2011
DOI: 10.1117/1.3520130
|View full text |Cite
|
Sign up to set email alerts
|

Design and validation of an angle-resolved low-coherence interferometry fiber probe for in vivo clinical measurements of depth-resolved nuclear morphology

Abstract: Abstract. We present a novel Fourier-domain angle-resolved low-coherence interferometry (a /LCI) fiber probe designed for in vivo clinical application in gastrointestinal endoscopy. The a/LCI technique measures the depthresolved angular scattering distribution to determine the size distribution and optical density of cell nuclei for assessing the health of epithelial tissues. Clinical application is enabled by an endoscopic fiber-optic probe that employs a 2.3-m-long coherent fiber bundle and is compatible wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 37 publications
2
49
0
Order By: Relevance
“…Overall, the results presented corroborate the fact that a depth-specific analysis is necessary to fully map the scattering properties of epithelial tissues [4,31,32]. While previous studies have revealed a layer-to-layer variation in scattering strength, a similar trend is also evident here for other intensity and shape metrics computed from two-dimensional patterns.…”
Section: Discussionsupporting
confidence: 71%
“…Overall, the results presented corroborate the fact that a depth-specific analysis is necessary to fully map the scattering properties of epithelial tissues [4,31,32]. While previous studies have revealed a layer-to-layer variation in scattering strength, a similar trend is also evident here for other intensity and shape metrics computed from two-dimensional patterns.…”
Section: Discussionsupporting
confidence: 71%
“…a/LCI clinical system schematic in a Mach-Zehnder interferometer geometry. The fiber probe tip shows the sample illumination by the PM fiber and scattered light collected through the fiber bundle [17].…”
Section: Clinical A/lci Studymentioning
confidence: 99%
“…1 and described in detail by Zhu, et al [17]. Briefly, an 830 nm superluminescent diode (Superlum, Moscow, Russia) is used in a Mach-Zehnder interferometer geometry.…”
Section: Clinical A/lci Studymentioning
confidence: 99%
“…These measurements were subracted from all subsequent ones in order to isolate the interference term. Next, the interference spectrum was remapped onto a linear wavenumber axis and a phase correction was applied to compensate for any dispersion imbalance between the sample and reference arms [22,23]. Finally, the processed interference spectrum was Fourier transformed to determine the depth-resolved reflectivity of the sample.…”
Section: Data Processingmentioning
confidence: 99%